Pengaruh Penambahan Tepung Mokaf Tehadap Tingkat Kesukaan Konsumen Pada Kerupuk Biji Durian: The Effect of Adding Mokaf Flour on the Level of Consumer Favor on Durian Seed Crackers - Dwi Ari Cahyani (Universitas Merdeka Madiun, 2023)
Crackers are a type of snack that is favored by consumers of all ages. Crackers can be consumed directly as a snack or as a side dish. One of the factors that determine the quality of crackers is the crispness. Durian is one of the many local fruits produced in Banjarnegara Regency. Durian consists of skin, flesh and seeds. When the durian season arrives, the seeds and skin of the durian become waste that is not utilized. The nutritional content of durian seeds which is quite a lot can be used as processed food that can be consumed by the community. Mocaf flour (Modified cassava flour) is a flour product derived from cassava which is processed using the principle of modifying cassava cells by fermentation. Based on the background of previous research results, it can be formulated the problem that underlies this research, namely how the right composition of durian seeds and mokaf flour and the length of time for boiling durian seeds to produce durian seed crackers are favored by consumers. This study aims to determine the level of consumer preference from the taste, color, texture and aroma of the durian seed crackers produced. This study used fresh durian seeds collected at durian sellers in the Sigaluh area, Banjarnegara Regency. The research was carried out at the Agricultural Product Processing Laboratory and Production Unit of the Banjarnegara Polytechnic Agroindustry Study Program. This study applies experimental research methods. The experimental design used was a completely randomized design with 3 replications. The hedonic test used 25 semi-trained panelists and the test results were analyzed using Anova. Furthermore, a follow-up test was used to determine whether there was a significant difference between the various treatments using the DMRT (Duncan Multiple Range Test) test. The results showed that the panelists preferred mokaf durian seed crackers which were processed with 100% durian seeds boiled by boiling for 30 minutes without the addition of mokaf flour. The panelists' preference for the color of the durian seed crackers was significantly different when the durian seeds were boiled for 30 minutes. While the aroma of the durian seed crackers produced is significantly different from the crackers by boiling for 30 minutes